THE IMPLEMENTATION OF PIG FARMING MAINTENANCE MANAGEMENT IN SAMBIRENTENG VILLAGE TEJAKULA DISTRICT BULELENG REGENCY - I M., Reynaldo; Inggriati, N. W. T.; Suarta, G. (Jurnal Peternakan Tropika; Vol 10 No 1 (2022): Vol. 10 No. 1 Tahun 2022; January - april, 2022)
This research aims to find out the implementation level of pig farming management and the factors related to the implementation level of pig farming management. It was conducted in Sambirenteng Village, Tejakula District, Buleleng Regency, for three months, from February till April 2021. The location and respondents of this research were determined using the purposive sampling method. There were 35 respondents determined by quota sampling. Rank-Spearman Correlation Coefficient (Siegel, 1997) method was applied in this research to identify the factors related to the implementation of pig farming management. The results showed that the implementation of pig farming management in Sambirenteng Village belongs to a low level. The factors such as age, formal education, time to farm the pigs, land area owned, and creativity have unreal relation (p>0,05) to the implementation of pig farming management. On the other hand, non-formal education, attitude, and knowledge have a real relationship (p<0,01). The conclusion: 1) The implementation level of pig farming management in Sambirenteng Village is still at the low level. 2) The factors related to the implementation level of pig farming management are non-formal education, attitude, and knowledge. Suggestion: The local government can provide counseling about the implementation of pig farming management in Sambireng Village through individuals and groups in order to improve skills, knowledge, and maximize farming results. Keyword : factors, attitudes, knowledge, counseling